Does Race Matter? Earnings of Visible Minority Graduates from Alberta Universities - Maximova, Katerina; Krahn, Harvey (Canadian Journal of Higher Education, 2005)
Using data from the 1997 Alberta University Graduate Survey, this study compares earnings of visible minority graduates and their non-visible minority counterparts who received degrees in 1994. The central question is whether investments in human capital in the form of Canadian post- secondary education by visible minority members and other graduates yield similar returns in the Canadian labour market. Multiple regression analysis results indicate that earnings of visible minority graduates do not differ significantly from those of other graduates, although several interesting interaction effects are observed. Overall, this study provides no evidence of racial discrimination against visible minority members who obtained their post-secondary educational credentials in Alberta.